Platforms for Investigating LncRNA Functions - Charles Richard, J.; Eichhorn, Pieter (2018)
© 2018, Society for Laboratory Automation and Screening. Prior to the sequencing of the human genome, it was presumed that most of the DNA coded for proteins. However, with the advent of next-generation sequencing, it has now been recognized that most complex eukaryotic genomes are in fact transcribed into noncoding RNAs (ncRNAs), including a family of transcripts referred to as long noncoding RNAs (lncRNAs). LncRNAs have been implicated in many biological processes ranging from housekeeping functions such as transcription to more specialized functions such as dosage compensation or genomic imprinting, among others. Interestingly, lncRNAs are not limited to a defined set of functions but can regulate varied activities such as messenger RNA degradation, translation, and protein kinetics or function as RNA decoys or scaffolds. Although still in its infancy, research into the biology of lncRNAs has demonstrated the importance of lncRNAs in development and disease. However, the specific mechanisms through which these lncRNAs act remain poorly defined. Focused research into a small number of these lncRNAs has provided important clues into the heterogeneous nature of this family of ncRNAs. Due to the complex diversity of lncRNA function, in this review, we provide an update on the platforms available for investigators to aid in the identification of lncRNA function.